Teej Songs: Narrative Performance, Resistance and Healing - Neupane, Pimala; Neupane, Rajendra (Kalika Journal of Multidisciplinary Research, 2025)
This research paper argues that contemporary Nepali Hindu women challenge patriarchal norms and Hindu ritual practices, which dominate them and marginalize them, through the narrative performance of the Teej songs. This paper examines four contemporary Teej songs, which narrate the traumatic experience of married Nepali Hindu women, and their performances in accompanying music videos, recorded, produced, and uploaded on YouTube in 2024 and 2025. Drawing on the duo of performance theory and scriptotherapy, this paper conducts an analytical and interpretative study of the selected songs, discussing how the women dramatize their individual and collective traumatic experience, not only as a form of resistance to patriarchal and cultural norms, but also as a process of healing. In the process, the duo explores and analyzes both the performance and the lyrics of the selected songs, where Schechner’s performance theory focuses on women’s performance, and Henke’s scriptotherapy focuses on the narrative/storytelling of the lyrics of the songs. This paper addresses an existing research gap and contributes to scholarship in the area of study. This qualitative research offers a novel perspective to future researchers for their scholarly engagement in the field of literary and cultural criticism.